1966
DOI: 10.1113/jphysiol.1966.sp007894
|View full text |Cite
|
Sign up to set email alerts
|

Central pathways of some autonomic reflex discharges

Abstract: 6. Such evidence led to the conclusion that there are two pathways for reflex discharge into inferior cardiac and renal nerves, one involving a supraspinal relay and the other confined to the spinal cord.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
29
1

Year Published

1969
1969
2015
2015

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 110 publications
(34 citation statements)
references
References 20 publications
(26 reference statements)
4
29
1
Order By: Relevance
“…The present study describes some of these effects in the absence of other known cardiovascular stimuli. The findings are relevant to other studies which have demonstrated a variety of polysynaptic somatovisceral reflexes following stimulation of somatic afferent nerves in intact and spinal animals (Johansson, 1962;Coote & Downman, 1966;Franz, Evans & Perl, 1966).…”
Section: Introductionmentioning
confidence: 60%
“…The present study describes some of these effects in the absence of other known cardiovascular stimuli. The findings are relevant to other studies which have demonstrated a variety of polysynaptic somatovisceral reflexes following stimulation of somatic afferent nerves in intact and spinal animals (Johansson, 1962;Coote & Downman, 1966;Franz, Evans & Perl, 1966).…”
Section: Introductionmentioning
confidence: 60%
“…When the spinal cord was intact, F 104 W. C. DE GROAT AND R. W. RYALL the latency of reflex excitation was sufficiently long to allow for conduction of impulses to and from the brain-stem and it is suggested that the reflex is a long-loop reflex involving supraspinal centres. Similar, longlatency responses in the sympathetic (Coote & Downman, 1966) and somatic (Shimamura et al 1964) nervous systems have also been attributed to reflexes involving supraspinal centres. However, the possibility that the late reflex discharge of sacral parasympathetic neurones is a spinal reflex which depends upon a tonic descending facilitation has not been entirely excluded.…”
Section: Discussionmentioning
confidence: 83%
“…For this purpose, the tip of a cooling probe (2-5 mm o.d.) maintained at 0°C, similar to that described by Coote & Downman (1966), was placed on the floor of the fourth ventricle in the mid-line, 1-0 mm rostral to obex. A sequence of ten averaged spinally evoked responses was repeated 6 times before and then when the medulla had been cooled, and subsequently on recovery from cooling.…”
Section: Resultsmentioning
confidence: 99%